Effect of pretransplant dialysis vintage on clinical outcomes in deceased donor kidney transplant - Jeong-Hoon Lim; Yena Jeon; Deok Gie Kim; Yeong Hoon Kim; Joong Kyung Kim; Jaeseok Yang; Myoung Soo Kim; Hee-Yeon Jung; Ji-Young Choi; Sun-Hee Park; Chan-Duck Kim; Yong-Lim Kim; et al. (Scientific Reports, 2022)
Abstract The waiting time for deceased donor kidney transplants (DDKT) is increasing. We evaluated DDKT prognosis according to the pretransplant dialysis vintage. A total of 4117 first-time kidney transplant recipients were enrolled from a prospective nationwide cohort in Korea. DDKT recipients were divided into tertiles according to pretransplant dialysis duration. Graft failure, mortality, and composite were compared between DDKT and living donor kidney transplant (LDKT) recipients. Pretransplant dialysis vintage was longer annually in DDKT recipients. In the subdistribution of the hazard model for the competing risk, the first tertile did not show an increased risk of graft failure compared with LDKT recipients; however, the second and third tertile groups had an increased risk of graft failure compared to LDKT recipients (adjusted hazard ratio [aHR] 3.59; 95% confidence interval [CI] 1.69–7.63; P < 0.001; aHR 2.37; 95% CI 1.06–5.33; P = 0.037). All DDKT groups showed a significantly higher risk of patient death than LDKT, with the highest risk in the third tertile group (aHR 11.12; 95% CI 4.94–25.00; P < 0.001). A longer pretransplant dialysis period was associated with a higher risk of the composite of patient death and graft failure in DDKT recipients. DDKT after a short period of dialysis had non-inferior results on graft survival compared with LDKT.